The Circulating Concentration of Adiponectin in Postmenopausal Women with and without Osteoporosis. (Journal of the College of Basic Education, 2023)
The current study was carried out to evaluate serum adiponectin level in osteoporosis postmenopausal women, as well as to investigate a possible correlation between adiponectin, calcium, phosphorus and alkaline phosphatase. There are few studies on the effects of adiponectin on bone metabolism.Osteoporosis is a common disease among postmenopausal women. Osteoporosis is a bone disorder in which bone mass in the body decreases.postmenopausal non-diabetic 30 women were selected from Baghdad teaching hospital over the period November 2010- April 2011 with the clinical diagnosis of osteoporosis (mean age 60.93 ± 6.21; rang 49 to 70 years). 30 postmenopausal non-diabetic women serve as control (mean age 59.17 ± 4.0; range 55 to 68 years). This study was included normal BMI in both patients and control groups. Serum adiponectin level was measured by ELISA technique, while colorimetric method was used to determine serum calcium, phosphorus and alkaline phosphatase.Serum adiponectin in osteoporosis postmenopausal non-diabetic women was significantly higher than postmenopausal non-diabetic women without osteoporosis (p<0.01).